Molecular Profiling–Based Precision Medicine in Cancer: A Review of Current Evidence and Challenges - Zhang, Qi; Fu, Qihan; Bai, Xueli; Liang, Tingbo (Frontiers in Oncology, 2020)
Matched therapy base on the next-generation sequencing (NGS) test is now part of routine care to guide treatments of patients with advanced solid tumors. However, whether and to what extent patients can benefit from this strategy on a large scale still remains uncertain. We review literatures on this topic to summarize the efficacy and limitations of this treatment strategy. We also discuss some important issues which need to be paid attention to in the future application of NGS in cancer treatment.